1982
DOI: 10.1002/ijc.2910300310
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of antigen‐induced leukocyte adherence inhibition by metabolites of arachidonic acid and intracellular nucleotides

Abstract: After binding a sensitizing tumor antigen, human leukocytes undergo a series of changes that lead to a loss of their glass-adherent properties; a phenomenon called leukocyte adherence inhibition (LAI). After surgery or when patients have a large tumor burden, their test results become negative. This study shows that in vitro incubation of the leukocytes for 5 min with PGE2 converted to positive the negative test, in an immunologically specific manner. The effect was critically dose-dependent, too little or too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1982
1982
1986
1986

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
(9 reference statements)
1
11
0
Order By: Relevance
“…As little as lo4 M FTL 55712 completely blocked 2.5 X M LTC,, and as little as M FPL 55712 had a similar effect when 2 X lo-" M LTD4 was used. Since we had shown previously that as little as M FPL 55712 was able to inhibit a positive LA1 response (Thomson et a/., 1982), it suggested that as little as 2 X 10-l1 M LTD, produced by monocytes was sufficient to mediate the inhibition of adherence of leukocytes to glass when they bind a sensitizing tumor antigen.…”
Section: O Ltc Ltdmentioning
confidence: 98%
See 2 more Smart Citations
“…As little as lo4 M FTL 55712 completely blocked 2.5 X M LTC,, and as little as M FPL 55712 had a similar effect when 2 X lo-" M LTD4 was used. Since we had shown previously that as little as M FPL 55712 was able to inhibit a positive LA1 response (Thomson et a/., 1982), it suggested that as little as 2 X 10-l1 M LTD, produced by monocytes was sufficient to mediate the inhibition of adherence of leukocytes to glass when they bind a sensitizing tumor antigen.…”
Section: O Ltc Ltdmentioning
confidence: 98%
“…Antigen-induced leukocyte adherence inhibition is blocked by drugs that block 5-lipoxygenase but not the cyclooxygenase pathway of arachidonic acid metabolism (Thomson et al, 1982). The LA1 phenomenon is prevented by FPL 55712, an antagonist of SRS, suggesting that slow-reacting substances of anaphylaxis (SRS-A), or leukotrienes, are responsible for mediating the LA1 phenomenon (Thomson et al, 1982).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The same OSN as well as crude extracts from liver metastasis were able to generate the LAI phenomenon. The latter is induced by an arachidonic acid metabolite and is modulated by cyclic AMP levels [17], It is hence not surprising to note that PGE2, which is able to elevate cyclic AMP levels, may have a crucial efTcct on the performance of the LAI assay [18]. In view of the broader knowledge about the LAI phenomenon our results should be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal lungs of 14 to 19 weeks express the OSN epitope, but fetal lungs of 20 weeks do not (Thomson, 1982b), suggesting that the OSN epitope of p40 is expressed during early fetal development and again during oncogenesis. It is not known whether p40 molecules without the OSN epitope are expressed by normal lung tissue.…”
Section: Discussionmentioning
confidence: 99%